Roma immigrants in the countries of Western Europe. The case of France and Italy = Romscy imigranci w państwach Europy Zachodniej - przypadek Włoch i Francji - Talewicz-Kwiatkowska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The expansion of the European Union and the accession of ten new EU member states in 2004 as well as the accession of Bulgaria and Romania in 2007 meant that the new borders of the EU came to encompass most of the Roma minorities living on the Old Continent. The Roma, as well as being the largest ethnic group in modern Europe, are also its most marginalised group. |ey have been and continue to be ostracised, excluded from society, and discriminated against on all possible social levels.
Keywords: Roma; Gypsies; integrity; immigrants; Romowie; Cyganie; imigranci; integracja